Sociology of Interdisciplinarity The Dynamics of Energy Research - Silvast, Antti (Springer Nature, 2022)
This Open Access book builds upon Science and Technology Studies (STS) and provides a detailed examination of how large-scale energy research projects have been conceived, and with what consequences for those involved in interdisciplinary research, which has been advocated as the zenith of research practice for many years, quite often in direct response to questions that cannot be answered (or even preliminarily investigated) by disciplines working separately. It produces fresh insights into the lived experiences and actual contents of interdisciplinarity, rather than simply commentating on how it is being explicitly advocated. We present empirical studies on large-scale energy research projects from the United Kingdom, Norway, and Finland. The book presents a new framework, the Sociology of Interdisciplinarity, which unpacks interdisciplinary research in practice. This book will be of interest to all those interested in well-functioning interdisciplinary research systems and the dynamics of doing interdisciplinarity, including real ground-level experiences and institutional interdependencies.